Gender & difference in a globalizing world twenty-first century anthropology - Mascia-Lees, Frances E. (Waveland Press, 2010)
"Mascia-Lees'... ability to synthesize ideas rewards readers wih a text that clearly conceptualizes how differences of gender, race, class, and sexuality structure today's complex globalizing world. It exposes the strengths and weaknesses of different theoretical orientations used in anthropology to study gender, difference, power, and inequality including feminist anthropology; black feminist anthropology; lesbian/gay/bisexual/transgendered theory; practice, postcolonial, symbolic, and psychological anthropology; as well as social evolutionism, sociobiology, and evolutionary pscyhology, among others"
Keywords: afro-féminisme; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; intersectionnalité; premier cycle; queer; sciences humaines; sex1911; sex2283; thématiques; travail

Queer Theory and Native Studies: The Heteronormativity of Settler Colonialism - Smith, A. (GLQ -NEW YORK-, 2010)
Queer studies highlights the importance of developing analyses that go beyond identity and representational politics. For Native studies in particular, queer theory points to the possibility of going beyond representing the voices of Native peoples, a project that can quickly become co-opted into providing Native commodities for consumption in the multicultural academic-industrial complex. The subjectless critique of queer theory can assist Native studies in critically interrogating how it could unwittingly re-create colonial hierarchies even within projects of decolonization. This critique also sheds light on how Native peoples function within the colonial imaginary-including the colonial imaginary of scholars and movements that claim to be radical. At the same time, Native studies can build on queer of color critique's engagement with subjectless critique. In the move to go "postidentity," queer theory often reinstantiates a white supremacist, settler colonialism by disappearing the indigenous peoples colonized in this land who become the foils for the emergence of postcolonial, postmodern, diasporic, and queer subjects. With respect to Native studies, even queer of color critique does not necessarily mark how identities are shaped by settler colonialism. Thus a conversation between Native studies and queer theory is important, because the logics of settler colonialism and decolonization must be queered in order to properly speak to the genocidal present that not only continues to disappear indigenous peoples but reinforces the structures of white supremacy, settler colonialism, and heteropatriarchy that affect all peoples.
Keywords: amériques; approches et analyses; colonialisme; communication; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; militance; premier cycle; queer; régions géographiques; sciences humaines; soc2014; suprématie blanche; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études culturelles